2019
DOI: 10.12968/bjon.2019.28.17.s16
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre review of readmission rates within 30 days of discharge following lung cancer surgery

Abstract: Postoperative complications following curative lung cancer surgery are well recognised, but there is limited data on 30-day readmission rates. The UK Thoracic Surgery Group conducted a multicentre review over a 3-month period to assess readmission rates. Overall readmission among the 268 patients who had undergone primary lung cancer surgery was 30 (11%); 14/30 of readmissions occurred within 7 days of discharge, with 13/30 patients readmitted to a hospital that had not performed the surgery. The causes of rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The screening process is shown in Figure 1. Finally, 11 articles were included in our study, 4,[6][7][8][13][14][15][16][17][18][19] involving a total of 386 012 participants. Of the 386 012 patients, 26 465 underwent readmission, while 359 547 did not undergo readmission.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…The screening process is shown in Figure 1. Finally, 11 articles were included in our study, 4,[6][7][8][13][14][15][16][17][18][19] involving a total of 386 012 participants. Of the 386 012 patients, 26 465 underwent readmission, while 359 547 did not undergo readmission.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Recent studies have shown that readmission rates among oncology patients vary between 13.8% to 30%, some of which are preventable [ 22 , 51 , 52 , 53 ]. Hospital readmission rates have been shown to vary by type of cancer (highest rates of non-elective readmissions occurred among bladder, pancreatic, ovarian and liver cancer patients), treatment (surgical vs. chemotherapy), disease stage, presence of co-morbidities, longer LOS, and increased age [ 20 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical causes for non-elective readmissions among oncology patients include postoperative complications (for example, infection and surgical wound complications), poorly controlled pain, malnutrition or dehydration due to nausea, vomiting and/or diarrhoea, failure to thrive and lack of readiness for discharge [ 22 , 53 , 54 ]. An association was observed between a first chemotherapy cycle, inpatient intravenous fluid use and antiemetic prescription use and increased non-elective hospital readmissions in older oncology patients (>60 years).…”
Section: Discussionmentioning
confidence: 99%
“…Even modest improvements in the PPC rate would have massive cost savings through reduction ITU admissions, hospital bed days used and readmission rates. In the UK, 30-day readmission to hospital after lung cancer surgery is high (12%) and is a key target for improvement in the national lung cancer audit 41 42. Thus, potential clinical and cost benefits to the NHS of optimising nutrition and so ameliorating major complications and hospital readmission are significant.…”
Section: Discussionmentioning
confidence: 99%